Pengaruh Self Confidence Dan Pendelegasian Wewenang Terhadap Kinerja Karyawan Pada PTPN IVMedan - Herdiyanti Herdiyanti; Muslim Wijaya; Teddi Pribadi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to find out whether self confidence has a positive and significant effect on employee performance at PT. Perkebunan Nusantara IV (Persero) Medan, to find out whether the delegation of authority has a positive and significant effect on the performance of employees at PT. Perkebunan Nusantara IV (Persero) Medan, and to find out whether self confidence and the delegation of authority have a positive and significant effect on the performance of employees at PT. Perkebunan Nusantara IV Medan. The population in this study were all employees of the Human Resource section at PT. Perkebunan Nusantara IV (Persero) Medan, amounting to 58 people. The sample in this study amounted to 58 people. this type of research is associative research to find out the effect of independent variables on the dependent variable, using multiple linear regression statistical analysis techniques. Then the research results obtained are self confidence has a positive and significant effect on employee performance, delegation of authority has a positive and significant effect on employee performance, then self confidence and delegation of authority have a positive and significant effect on employee performance at PT. Perkebunan Nusantara IV (Persero) Medan.